Post-Irradiation Ageing Effect on Morphological Characters of Crotalaria saltiana (Journal of Bio-Science, 2009)
Post-irradiation ageing effect on seed germinability and different morphological characters of Crotalaria saltiana were studied in the year of 2006. Germination percentage of Crotalaria saltiana seeds treated with different doses of gamma rays, aged for 32 years in moisture free condition showed remarkable variation. Plants grown from the treated seeds of all the doses showed diversity among themselves regarding their morphological characters. Such as plant height was found to reduce in lower doses and this character showed no such consistent result. Leaf irregularities such as, invaginated margin, inverted margin with blunt apex, leaf with bifurcated apex, small size and dented margin, etc. were recorded. Key words: Post-irradiation ageing effect, Morphological characters, Crotalaria saltiana.   DOI:10.3329/jbs.v16i0.3747 J. bio-sci. 16: 89-93, 2008